English across borders: Higher education students’ perceptions of language policy and the global role of English - Khanaia Audria Titania; Aidil Syah Putra; Kayla Aulia (Universitas Merdeka Malang, 2026)
This study examines higher education students’ perceptions of language policy and the global role of English within contemporary educational contexts. Using a descriptive quantitative survey design, data were collected through a closed-ended questionnaire distributed to English education students. The study explores how English is perceived in relation to government language policy, formal education, and international communication. The findings indicate that most respondents perceive English as a policy-regulated language that holds a central position in compulsory education and international domains such as diplomacy, trade, and access to global information. Participants also recognize the influence of English on local and national languages and express support for bilingual or multilingual language policies involving English. These findings reflect students’ perceptions of English as a global lingua franca that offers educational and socio-economic opportunities while simultaneously raising concerns about linguistic balance and diversity. The study highlights the importance of developing inclusive language policies that integrate English alongside local languages to support global engagement without marginalizing linguistic diversity.